2020
DOI: 10.1158/1078-0432.ccr-19-3259
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Antigen Receptor-Glypican-3 T-Cell Therapy for Advanced Hepatocellular Carcinoma: Results of Phase I Trials

Abstract: Purpose: Our preclinical studies demonstrated the potential of chimeric antigen receptor (CAR)-glypican-3 (GPC3) T-cell therapy for hepatocellular carcinoma (HCC). We report herein the first published results of CAR-GPC3 T-cell therapy for HCC. Patients and Methods: In two prospective phase I studies, adult patients with advanced GPC3 þ HCC (Child-Pugh A) received autologous CAR-GPC3 T-cell therapy following cyclophosphamide-and fludarabine-induced lymphodepletion. The primary objective was to assess the treat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
156
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 227 publications
(174 citation statements)
references
References 42 publications
3
156
0
Order By: Relevance
“…(2/13). Compared to CAR-T targeting CD19 for hematological malignancies, CAR-T targeting GPC3 for hepatocellular carcinoma did not show encouraging e cacy [22]. Various factors affect the therapeutic bene t of CAR-T on HCC, such as a poor tumor tissue microenvironment that limits proliferation and CAR-T cytotoxicity and the dense ECM which limits lymphocyte in ltration into tumor tissue [13,25].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…(2/13). Compared to CAR-T targeting CD19 for hematological malignancies, CAR-T targeting GPC3 for hepatocellular carcinoma did not show encouraging e cacy [22]. Various factors affect the therapeutic bene t of CAR-T on HCC, such as a poor tumor tissue microenvironment that limits proliferation and CAR-T cytotoxicity and the dense ECM which limits lymphocyte in ltration into tumor tissue [13,25].…”
Section: Discussionmentioning
confidence: 98%
“…First, the editing of large genes is a major limiting factor when modifying T cells, as they increase the di culty of lentivirus packaging, reduce the ability of lentivirus to infect cells, and thus increase the cost of the procedure [29,30]. Secondly, GPC3 is reported to be a very speci c target, and thus CAR-T targeting of it is thought not to have off-target toxicity [22,31,32]. Therefore, we believe that for CAR-T targeting GPC3 or other speci c solid tumor targets, increasing CAR-T's in ltration ability is better than increasing its capacity for chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NCT02905188 and NCT03146234 studies ( Table 3 ) reported that patients with advanced GPC3+ HCC (Child-Pugh A), receiving autologous CAR-GPC3 T-cell therapy following cyclophosphamide and fludarabine had a tolerable toxicity profile with no grade 3/4 neurotoxicity. The OS rates at 6 months, 1 year, and 3 years were 50.3%, 42.0% and 10.5%, respectively, with a median OS of 9.1 months (95% CI: 1.5–20) [ 151 ]. The target lesions in two patients with partial response exhibited significant tumor shrinkage, while one patient with sustained stable disease was alive after 44.2 months [ 151 ].…”
Section: Adoptive Cell Transfer In Hepatocellular Carcinomamentioning
confidence: 99%
“…The OS rates at 6 months, 1 year, and 3 years were 50.3%, 42.0% and 10.5%, respectively, with a median OS of 9.1 months (95% CI: 1.5–20) [ 151 ]. The target lesions in two patients with partial response exhibited significant tumor shrinkage, while one patient with sustained stable disease was alive after 44.2 months [ 151 ]. Another phase I study (NCT02395250) [ 152 ] and a phase I/II study (NCT02723942) [ 153 ] have been completed; however, no results are yet posted.…”
Section: Adoptive Cell Transfer In Hepatocellular Carcinomamentioning
confidence: 99%